2005
DOI: 10.1002/ajh.20512
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of central venous catheter‐related thrombosis with minidose warfarin in patients treated with high‐dose chemotherapy and peripheral‐blood stem‐cell transplantation: Retrospective analysis of 228 cancer patients

Abstract: Patients with a central venous catheter (CVC) undergoing high-dose chemotherapy (HDC) followed by peripheral-blood stem-cell transplantation (PBSCT) for malignancies are at high risk of thrombosis, but the use of anti-coagulant prophylaxis remains debatable in this setting of patients. We analyzed the efficacy and the safety of minidose warfarin in 228 patients in whom CVCs had been placed and who had received 292 HDC courses of therapy. The catheters remained in place for a mean of 173 (range 40-298) days. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…However, their routine use is also linked to a number of CVC-related complications. Among the complications commonly reported in literature on Groshong CVCs, infections are the most frequent (0.1–11.5 per 1000 CVC days),5,6 although mechanical problems, including thromboembolic accidents, may occur at a non-negligible rate (1.2–13%) 7,8. However, these data primarily refer to adult patient populations with solid tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their routine use is also linked to a number of CVC-related complications. Among the complications commonly reported in literature on Groshong CVCs, infections are the most frequent (0.1–11.5 per 1000 CVC days),5,6 although mechanical problems, including thromboembolic accidents, may occur at a non-negligible rate (1.2–13%) 7,8. However, these data primarily refer to adult patient populations with solid tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Results reported in the literature show that the Broviac/Hickman device develops mechanical complications with a variable incidence of 1.3–10.1 episodes/1,000 CVC day (3,6–77,6% of CVC) 7,14…”
Section: Discussionmentioning
confidence: 99%
“…Oral anticoagulants are used therapeutically to reduce thromboembolic events. Warfarin examples include a reduction in catheter-related thrombosis (Guidry et al, 1991;Magagnoli et al, 2006); early venous thrombosis after operations (Calnan and Allenby, 1975;Pan et al, 2005), including hip surgery; atrial fibrillation (Middlekauff et al, 1995;Reiffel, 2000); and myocardial infarction (Asperger and Jursic, 1970). A number of adverse events have been recognized, most of which are related to drug interactions (Dayton and Perel, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…8 Studies have shown that patients undergoing hematopoietic stem cell transplant (HSCT) commonly develop CVC clots, which raises the question of whether thromboprophylaxis should be considered in this subset. 9 In a prospective trial evaluating the incidence of CVC thrombosis in patients with refractory lymphoma undergoing autologous stem cell transplantation, higher thrombosis rates were observed in those with Hodgkin's disease (59%) than in those with non-Hodgkin's lymphoma (25%). 10 The investigators speculated that the prolonged thrombocytopenia in HSCT patients might increase the risk of CVC thrombosis.…”
mentioning
confidence: 99%
“…10 The investigators speculated that the prolonged thrombocytopenia in HSCT patients might increase the risk of CVC thrombosis. 9 Therefore, current research continues to investigate the potential benefit of systemic anticoagulation for CVC thrombosis in HSCT patients. In addition, the seventh ACCP conference did not address the use of other systemic anti-coagulants, such as heparin infusion or direct thrombin inhibitors, for routine prophylaxis of CVC in cancer patients.…”
mentioning
confidence: 99%